Cu sub(3)(hexaiminotriphenylene) sub(2): An Electrically Conductive 2D Metal-Organic Framework for Chemiresistive Sensing - Campbell, Michael G; Sheberla, Dennis; Liu, Sophie F; Swager, Timothy M; Dinca, Mircea (Angewandte Chemie International Edition, 2015)
The utility of metal-organic frameworks (MOFs) as functional materials in electronic devices has been limited to date by a lack of MOFs that display high electrical conductivity. Here, we report the synthesis of a new electrically conductive 2D MOF, Cu sub(3)(HITP) sub(2) (HITP=2,3,6,7,10,11-hexaiminotriphenylene), which displays a bulk conductivity of 0.2Scm super(-1) (pellet, two-point-probe). Devices synthesized by simple drop casting of Cu sub(3)(HITP) sub(2) dispersions function as reversible chemiresistive sensors, capable of detecting sub-ppm levels of ammonia vapor. Comparison with the isostructural 2D MOF Ni sub(3)(HITP) sub(2) shows that the copper sites are critical for ammonia sensing, indicating that rational design/synthesis can be used to tune the functional properties of conductive MOFs. A MOF with a nose: Previous efforts to use metal-organic frameworks (MOFs) for chemical sensing have been hindered by poor signal transduction due to a lack of electrical conductivity. A new conductive 2D MOF can be used for the chemiresistive sensing of ammonia. It is shown that the sensing response can be varied by the choice of the metal node.